Analyzing the Correlation between the Level of Serum Markers and Ischemic Cerebral Vascular Disease by Multiple Parameters. (1st November 2015) - Dong, Laibin; Hou, Rongzhi; Xu, Yuxia; Yuan, Jiaying; Li, Lijun; Zheng, Chao; Zhao, Hehua
Abstract : Objective. To explore the serum markers associated with ischemic cerebral vascular disease (ICVD) and discuss their diagnostic value. Methods. Two hundred and eighty-eight patients with ICVD and one hundred and eighty healthy persons were enrolled as the case group and the control group, respectively. This paper then carried out the univariate and multivariate logistic regression analyses of their respective levels of serum markers, made combined analysis of related factors, and detected the diagnostic value. Results. Meta-analysis results showed that for ICVD patients the levels of CRP, S-100, TNF- α, HCY, NSE, and IL-6 were higher than those of the healthy persons, while the level of HDL was obviously lower than that of the healthy persons. The multivariate regression analysis indicated that the association between the level of HDL and TNF- α and the occurrence of ICVD was statistically significant (P < 0.05 ). The area under the curves (AUC) of receiver operating characteristic (ROC) curve of HDL and TNF- α was 0.916, with sensitivity of 90.91% and specificity of 76.47%. Conclusion. HDL has negative correlation with the occurrence of ICVD, while TNF- α was positively correlated with it. The combination test of HDL and TNF- α could raise the accuracy of ICVD diagnosis.